Variety of Languages in Marketing of Scarlett Skincare Products On Social Media Instagram - Lia Nurhalijah Amini; Rofi'atul Fadhillah; Ella Elvina Yuwono; Nabilah Rosa Azzahra; Cahya Wulandari; Endang Sholihatin (LPPM Institut Studi Islam Sunan Doe, 2024)
This study uses a method: quantitative data collection using a questionnaire. Based on this research, it can be concluded that: 1) Based on this research, it can be concluded that: 1) it is known that as many as 90.7% of the 54 respondents stated that the variety of languages in Scarlett's marketing on Instagram social media has a mixed variety of languages between standard and official languages; 2) it was known that 81.6% of the 54 respondents stated that the variety of languages used by Scarlett included: relaxed and friendly language, language of offers and promotions, descriptive language, inspirational language, humorous language; 3) it is known that 92.6% of 54 respondents stated that a variety of good and appropriate language is very important so that people can more easily understand products about their benefits and uses and can adapt them to the needs of each consumer. And with good language, it will also build a good brand image so that it can increase public trust in Scarlett's skincare products.